Record of performance testing program for beef cattle - Smith, W.; McAdams, V.E. (Kansas Agricultural Experiment Station, 2011)
Performance in beef cattle includes all traits that contribute to the efficient production of beef with quality appeal to the consumer. The systematic measurement of economically important production traits and the use of such procedures comprise what is known as Record of Performance. The goal of these procedures is to identify the genetically superior individuals within a herd so that maximum genetic improvement can be made through their selection and breeding. Performance should be a guide to beef herd improvement in Kansas.
Keywords: Beef; Performance; Genetics; Breeding